A Design of Web-Based Informatics Journal Information System - Sutrisna, Benedict Emanuel; Karyawati, AAIN Eka (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2021)
Informatics has become among the fastest growing studies with hundreds or more papers and journals being published each year. The ever expanding repository of published and unpublished journals makes it more and more difficult and expensive to manage it with only human capabilities. As such, the need for an information system that can help classify and manage journals and papers on informatics becomes more and more important. This paper discusses the design and implementation of an informatics journal information system using the prototype method and uniform modeling language.